Study of hydrocarbon compounds levels in water, sediments and some aquatic biota in Al-Mushrah river in Misan province/ Iraq - misanjas, Salih Hassan Jazza ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
In this study levels and sources of total petroleum hydrocarbon compounds (TPHs) and Polycyclic aromatic hydrocarbons (PAHs) were estimated in water , sediments and some aquatic biota which used as a bio-indictor to assess the pollution status of the water in Al-Mushrah river in Misan province.TPHs concentrations in water samples ranged from 0.759 to 2.476 μg/l ,whereas in sediment ranged from 1.55 to 3.408 μg/gm dry weight in station 1 and station 2 respectively .TPHs levels in plant species ranged from 4.222 to 13.985 μg/gm d.w in Phragmits australis and Ceratophyllum demersum respectively and in fish muscles ranged between 1.765 μg/gm d.w and 92.592 μg/gm d.w in Liza abu and Barbus luteus respectively ,while in tissues of Unio tigridis were 13.18 μg/gm d.w. Concentrations of total PAHs in water samples ranged between 18148.43 and 155416.327 ng/l ,whereas in sediments ranged between 10866.47 and 44417.53 ng/gm in St1 and St2 respectively .The levels of low molecular weight PAHs(LPAHs) in water and sediment samples were less than high molecular weight PAHs (HPAHs). Sources of PAHs in water samples were pyrogenic origin, whereas in sediments samples were petrogenic. Total PAHs recorded in plant species ranged between 18532.11984 ng/gm and 123631.6954 ng/gm in P. australis and C. demersum ,sources of PAHs in plants were petrogenic and in fish samples total PAHs ranged from 51161.66 to 358080.1 ng/gm in L. abu and B. luteus respectively, the fish samples in study area were very highly contaminated with PAHs according to Baumard et al (1998) classification ,sources of PAHs were in B. luteus were pyrogenic ,whereas in L. abu and Cyprinus carpio were petrogenic , while total PAHs in U. tigridis were 152462.93 ng/gm and sources of PAHs in U. tigridis were pyrogenic. High levels of TPHs and PAHs in studied aquatic biota observed in this study suggests that these organisms can be used as a tool for bio-monitoring of hydrocarbon pollution in study area